Proposed Approach for Analysing General Hygiene Information Using Various Data Mining Algorithms - Mustafa , Tareef K. (Iraqi Journal of Science, 2022)
General medical fields and computer science usually conjugate together to produce impressive results in both fields using applications, programs and algorithms provided by Data mining field. The present research’s title contains the term hygiene which may be described as the principle of maintaining cleanliness of the external body. Whilst the environmental hygienic hazards can present themselves in various media shapes e.g. air, water, soil…etc. The influence they can exert on our health is very complex and may be modulated by our genetic makeup, psychological factors and by our perceptions of the risks that they present. Our main concern in this research is not to improve general health, rather than to propose a data mining approach that will eventually give a more clear understanding and automotive general steps that can be used by the data analyser to give more enhanced and improved results than using typical statistical tests and database queries. This research proposes a new approach involving 3 algorithms selected from data mining which are association rule mining, Apriori algorithm and Naïve Bayesian consequently, to offer a final improved decision support results that can serve the researchers in their fields.